Aggregate Investor Confidence in the Stock Market. Issue 4 (2nd October 2018) - Meier, Chris
ABSTRACT: Overconfidence is one of the most robust findings in the field of behavioral finance, and is associated with excessive trading and risk taking among market participants. Assessment of the level of confidence of individuals in their abilities and skills is well documented. However, the literature lacks an aggregate measure of investor confidence, with this required to test its implications on a macro level. The author introduces a simple measure of aggregate investor confidence by adopting a formal model of overconfidence. The applications of the measure suggest that, in aggregate, higher trading activity occurs when investor confidence soars, particularly for smaller stocks. Subsequently, the effect partially reverses, implying a correction to an initial overreaction. The newly introduced investor confidence index possesses better ability to predict trading activity than past returns, as used in prior studies. Additionally, investors tend to have a higher risk appetite when confident, as shown by increased investment in small stocks with higher risk.